Analisis makna peribahasa dalam laman sosial Facebook / Huraizah Abd Sani - Huraizah , Abd Sani (2017)
Malay proverbs have developed latest phenomenon within today’s community with different style of presentation compared to before. Noticed that there is lacking in the use of proverbs among community these days is the starting point of this study. This study was carried out to explore the changes and relevance in practicing proverbs among current community. This study focus on Facebook users because it plays an important role in connecting people and it is spread across the whole world rapidly. Despite the fact that communicating using proverbs is not trending, it is still unforgotten among our community nowadays and widely used in daily life. The main purpose in the use of proverbs is still intact by providing implicit and explicit values. A sample of 50 proverbs were taken from social media Facebook was reviewed and analyzed. The focus of this study was to review the changes in meaning of proverbs and its correlation to cognitive, collocation, lexical, and relevance of proverbs among current community. Based on the Relevance and Relativity Linguistics Theory, this study was conducted to see the changes in interpretation and the relevance of proverbs utilization within the community nowadays. The outcome of this study found that Malay proverbs was often used to describe point of view, sarcasm, to teach, and also as a protest against certain group of people. People develop great ideas in order to express thoughts in mind by using proverbs.